Factors affecting sustainable supply chains in industrial markets. Case study: Buyer-supplier relationships in German railway industry. - Zhamakochyan, Diana (My University, 2016)
Business activities within organizations can have a huge impact on global economy and future generations; especially MNCs are accountable for sustainability in supply chains. Sustainable supply chain management (SSCM) has emerged to focus organizations on all three dimensions of sustainable development, i.e. the combination of economic, environmental, and social performance, in supply chain management. Thereby, all aspects in the supply chain are aligned with environmental and social values. The engagement in SSCM practices becomes critically important for buyers and suppliers in B2B markets. A trustful relationship between supply chain partners aligned with support from top management is an important driver for SSCM. This qualitative study aims to investigate factors affecting sustainable supply chains in industrial markets. Moreover, its goal is to examine the role of trust between buyers and suppliers in sustainable supply chains. Multiple case studies were conducted based on four case companies, two SMEs and two MNCs, from the railway industry in Germany. Semi-structured interviews with managers served as a basis to analyze trust in buyer-supplier relationships and sustainability in supply chains. The results show that buying companies experience pressure from their customers to follow the guidelines and requirements related to sustainability. Therefore, focal companies demand management systems, such as ISO 14001 or the code of conduct, from their suppliers. The findings for SMEs show, that the supplier will not necessarily engage in SSCM, if the customer does not demand sustainability. In contrast, MNCs engage in SSCM due to their company’s sustainability approach. In addition, barriers and supporting factors for SSCM are identified. The results indicate no significant impact of trust on the decision to implement SSCM. Furthermore, the study provides practical implications for companies and managers: they should increase the awareness for sustainability aspects in supply chains and adopt a proactive B2B marketing strategy for sustainable supply chains.
Keywords: Sustainable Supply Chain; Sustainability; Inter-Organizational Trust; Buyer-Supplier Relationship; Industrial Market; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|